Data replication model for remote procedure call transactions - Deris, Mustafa Mat; Mamat, A; Surip, M; Khalid, S (WSEAS, 2005)
Remote Procedure Call (RPC) is the most popular model to facilitate the building of distributed programs. However, it only provides a restricted availability of update operations and does not support fault-tolerant. The combination of RPC and data replication techniques has been developed to support fault-tolerant from Remote Procedure Call (RPC). However, different data replication techniques provide a different availability and fault-tolerant. This paper proposes a data replication technique called Three Dimensional Grid Structure (TDGS) to form a high availability and fault-tolerant of RPC in distributed computing environment. Fault-tolerant programs developed in this environment are able to tolerate failures such as server failure, site failure or even network partitioning. In order to obtain the proposed programs, firstly we generalize the Three Dimensional Grid Structure protocol to provide high availability of read and write operations. Secondly, the replica management to support the development of reliable services in a replicated-server environment is established.